Bond strength between a polymer-infiltrated ceramic network and a composite for repair: effect of several ceramic surface treatments - Silva, Pollyanna Nogueira Ferreira da; Martinelli-Lobo, Carolina Machado; Bottino, Marco Antonio; Melo, Renata Marques de; Valandro, Luiz Felipe (FapUNIFESP (SciELO), 2018)
The effects of several ceramic surface treatments on bond strength of a polymer-infiltrated ceramic network and resin composite as repair material were evaluated. CAD-CAM blocks of a polymer-infiltrated ceramic network (Vita Enamic) were sliced and subjected to aging process, followed by embedding in acrylic resin. The bonding/repair area was treated as follows (n = 30): C- without treatment; UA- universal adhesive application; FM- 10% hydrofluoric acid and silane application; OM-airborne-particle abrasion with aluminum oxide and silane application; RP- tribochemical silica coating; and CA- surface grinding and application of universal adhesive. Composite resin cylinders were made on the treated surface. Specimens from each group were assigned randomly to two subgroups (n = 15) considering storage condition: Baseline (shear tests after 48 hours) or Storage (tests after 6 months under distilled water). The treated surfaces were analyzed by goniometry, roughness, and SEM. Two-way ANOVA and 1-way ANOVA were applied to analyze the bond data and roughness / contact angle data, respectively, followed by Tukey's test (α = 5%). Surface treatments and storage conditions affected bond strengths (p < 0.01). Surface grinding (CA) followed by universal adhesive promoted the highest value of bond strength (14.5 ± 4.8 MPa for baseline, 8.5 ± 3.4 MPa for storage) and the roughest ceramic surface. Grinding with silicon carbide paper (simulating diamond bur) followed by the application of a universal adhesive system is the best option for repairing fractures of the polymer-infiltrated ceramic network.